Optical spectroscopy and frequency upconversion properties of Tm3+ doped tungstate fluorophosphate glasses - Poirier, G.; Jerez, V. A.; de Araujo, C. B.; Messaddeq, Younes [UNESP]; Ribeiro, SJL; Poulain, M. (American Institute of Physics (AIP), 2003)
Tungstate fluorophosphate glasses of good optical quality were synthesized by fusion of the components and casting under air atmosphere. The absorption spectra from near-infrared to visible were obtained and the Judd-Ofelt parameters determined from the absorption bands. Transition probabilities, excited state lifetimes and transition branching ratios, were, determined from the measurements. Pumping with a 354.7 nm beam from a pulsed laser. resulted in emission at 450 nm. due to transition D-1(2)-->F-3(4) in Tm3+ ions and a broadband emission centered at approximate to 550 nm attributed to the glass matrix. When pumping at 650 nm, two emission bands at 450 nm (D-1(2)-->F-3(4)) and at 790 nm (H-3(4)-->H-3(6)) were observed. Excitation spectra were also obtained in order to understand the origin of both emissions. Theoretical and experimental lifetimes were determined and,the results were explained in terms of multiphonon relaxation. (C) 2003 American Institute of Physics.